Molecular characterization of a lineage negative stem-progenitor cell population from human peripheral blood - Siti Norhaiza, H.; Intan Zarina, Z.A.; Rohaya, M.A.W.; Sahidan, S.; Shahrul Hisham, Z.A. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Current haematopoietic stem cell transplantation protocols rely heavily upon CD34+ cells to estimate haematopoietic stem and progenitor cell yield. However, several studies nowadays emerged with evidence that CD133+ cells represent a more primitive cell population than their CD34+ counterparts. The objective of the present study was to isolate CD133+ stem cells by a rapid negative isolation method which depletes human peripheral blood mononuclear cells (MNCs) from cells expressing haematopoietic lineage markers CD2, CD3, CD11b, CD14,CD15, CD16, CD19, CD56, CD123, and CD235a and isolates a discrete lineage negative (Lin-) cell population (11±2% of MNC, n=6). Human peripheral blood MNCs were fractionated by density gradient centrifugation. After labelling with antibody against haematopoietic lineage markers, MNCs were subjected to magnetic assisted cell sorting (MACS). The expression of stem cells markers was examined by reverse transcriptase PCR (RT-PCR). We showed that Lin- stem-progenitor cell population encompassed the common markers used to characterize adult stem cells including SLAMF1, CD90 and CD133 and was also enriched for CD117, a surface receptor for stem cell factor. This cell population is more homogenous and primitive as compared to suspension MNCs which comprised of SLAMF1 and CD117 but the cells with haematopoietic lineage marker, CD14 and CD2 were also present. In conclusion, our approach was able to isolate a homogenous Lin– stem-progenitor cell population from human peripheral blood hence offers a promising alternative to current haematopoietic stem and progenitor selection methods.